Pengembangan Modul Pembelajaran Berbasis Media Sosial Instagram Pada Mata Pelajaran Kimia Kelas X SMA N 1 Kecamatan Kapur IX - najmiatul fajar (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
Abstract. The problem behind this research is the unavailability of effective, efficient, and interesting teaching materials. Students’ interest in learning teaching materials used during the learning process at school only use book in the library sucs as textbooks and teachers also have not developed other teaching meterials that can attract students’ interest in learning so that students cannot study independently at home and students use more internet for learning and playing social media at home rather than studying based on this, the researchers conduted research on the Development Of Instagram Social Media-Based Learning Modules on the material for the development of the periodic table of elements and for class X SMA/MA students. Through learning modules based on social media instagram attention and Students’ interest in learning increases so that this also effects students scores for low to high. The type of research used in this research is research and development of R&D (research and development) and the research model used is the 4D model (define, design, develop dan disseminate). To find out the validity or practicality of a learning module, the validity and practicality of a product is tested. The result show that the validation of the instagram sosial media based learning module is very valid with a percentage of 95,4% and the practicality result are very practice with a percentage of 90% for students and 88,4% for teachers.Keywords: module, instagram social media, 4D model, validity, practicality